Income Smoothing: Can Firm Size as a Moderation - Achmad Chaedar Yasin Bakhtiar; Agrianti Komalasari; Liza Alvia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the effect of cash holding, leverage, profitability, and company size on income smoothing practices with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The results show that cash holding does not have a significant effect on income smoothing practices, because companies tend to use cash for operational needs, debt payments, and dividends, so it is not used for profit manipulation. On the contrary, profitability and leverage have a significant effect on income smoothing practices, where companies with low profitability and high leverage tend to engage in this practice to maintain their reputation and the stability of their financial statements. In addition, firm size does not moderate the effect of cash holding on income smoothing practices, indicating that larger company size does not affect management decisions in carrying out this practice. However, firm size strengthens the effect of profitability and leverage on income smoothing practices. The larger the company size, the higher the tendency of management to stabilize financial statements to maintain the company's image and the trust of stakeholders, especially creditors. These findings provide insight for investors and regulators in understanding the factors that influence income smoothing practices in the manufacturing sector.